Analysis of changes in corporate external guarantee behavior and the role of governance factors under economic policy uncertainty - Huang, Xiaodong; Zhao, Jiayi; Hu, Boqiang; Zhu, Chenzhi (International review of financial analysis, 2025)
This study utilizes quarterly data from China's A-share listed companies spanning the years 2010 to 2022 to investigate how economic policy uncertainty influences corporate external guarantee practices. The findings reveal that as economic policy uncertainty escalates, corporations tend to broaden the scope of their external guarantees. The underlying mechanism suggests that, firstly, banks respond to heightened economic policy uncertainty by elevating credit financing thresholds and restricting credit supply. Secondly, corporations, impacted by the broader macroeconomic environment, experience a decline in profitability and liquidity, prompting them to increase external guarantee activities as a means of securing external financing. Notably, for corporations with more proficient boards and stronger operational capabilities, the influence of economic policy uncertainty on their external guarantee practices is comparatively diminished. •Economic uncertainty boosts firms' external guarantees.•As economic uncertainty rises, enterprise liquidity falls, boosting external guarantees.•Economic uncertainty weakens profitability, boosting firms' external guarantees.•Better management governance reduces firms' sensitivity to economic policy uncertainty.